2005
DOI: 10.1074/jbc.m508362200
|View full text |Cite
|
Sign up to set email alerts
|

The Osmotic Activation of Transporter ProP Is Tuned by Both Its C-terminal Coiled-coil and Osmotically Induced Changes in Phospholipid Composition

Abstract: Transporter ProP of Escherichia coli (ProPEc) senses extracellular osmolality and mediates osmoprotectant uptake when it is rising or high. A replica of the ProPEc C terminus (Asp 468 -Arg 497 ) forms an intermolecular ␣-helical coiled-coil. This structure is implicated in the osmoregulation of intact ProPEc, in vivo. Like that from Corynebacterium glutamicum (ProPCg), the ProP orthologue from Agrobacterium tumefaciens (ProPAt) sensed and responded to extracellular osmolality after expression in E. coli. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
119
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 60 publications
(123 citation statements)
references
References 61 publications
3
119
1
Order By: Relevance
“…Recently we showed that the osmolality yielding half-maximal ProP activity (and hence the osmotic activation "threshold") increased in parallel with the proportion of CL when E. coli was cultivated in media of increasing osmolality. This suggested that CL modulates ProP function, adapting the osmolality range over which ProP activity is regulated to match ambient (growth) conditions (7). The C termini of E. coli ProP and its orthologues are longer than those of its paralogues (like LacY) (3,7).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Recently we showed that the osmolality yielding half-maximal ProP activity (and hence the osmotic activation "threshold") increased in parallel with the proportion of CL when E. coli was cultivated in media of increasing osmolality. This suggested that CL modulates ProP function, adapting the osmolality range over which ProP activity is regulated to match ambient (growth) conditions (7). The C termini of E. coli ProP and its orthologues are longer than those of its paralogues (like LacY) (3,7).…”
mentioning
confidence: 99%
“…ProP orthologues with and without C-terminal coiled-coils are osmosensory transporters but orthologues and variants with the coiled-coil activate at lower osmolalities than those without (7). Mutations that disrupt or eliminate the coiled-coil raise the activation threshold (7,25,29). Thus the coiled-coils present on some ProP orthologues tune them to osmoregulate at low osmolalities (7).…”
mentioning
confidence: 99%
See 3 more Smart Citations